Caracterização molecular dos vírus do grupo Gamboa (Bunyaviridae, Orthobunyavirus) isolados nas américas e infecção experimental em pintos (Gallus gallus domesticus) com o vírus Gamboa cepa Be AN 439546 - CHIANG, Jannifer Oliveira (Universidade Federal do Pará, 2014)
Presently, little information on Gamboa serogroup viruses (Bunyaviridae, Orthobunyavirus) is available. Thus, in this work, it was performed a comparative phylogenetic study on the members of the Gamboa serogroup and with other orthobunyaviruses to the level of the gene Gn (M-RNA); an experimental infections in the domestic bird (Gallus domesticus) using the strain Be AN 439546 of the Gamboa Virus (GAMV); and a serologic study using the Hemagglutination Inhibition (HI) test in serum samples of wild animals and humans collected in Tucuruí - Pará. The phylogenetic analysis of Gamboa group viruses demonstrated that they are genetically closely related to group Turlock viruses and less related to the Simbu group viruses. The group Gamboa viruses were distributed in two clades (I and II), that it is in agreement with the current serologic classification; the clade I correspond to the Gamboa complex and the clade II to the Alajuela complex. The strain Be AN 439546 presented tropism for chikens lung and liver, with viral replication in this organs confirmed by detection of viral antigens by immunohistochemistry. These results, demonstrate that this bird species is a susceptible host for GAMV replication. The detection of HI antibodies against GAMV, confirmed by neutralization tests were found in wild bird plasmas and reinforces the hypothesis that these animals constitute the main amplification hosts in the maintenance cycle of GAMV. Full length genome studies of the Gamboa serogroup viruses, as well as on the ecoepidemiology of their vectors and potential vertebrate hosts are needed to generate new data and to reinforce the understanding of the information already existent on those viruses.